A study on dissolution rates of silver sulphadiazine microcapsules using different polymers / Nor Amlizan Ramli and Gary P. Martin - Ramli, Nor Amlizan; Gary, P. Martin (2004)
Microencapsulation is a novel method of drug delivery system that enables topically applied drugs to dissolve more efficiently when applied locally. The technique consists of encapsulating drugs in micron-sized capsules of barrier polymers. The function of polymer is to enhance the rate of drug dissolution. The objective of this research is to design microcapsules carrying silver sulphadiazine (AgSD) with two different polymers and to study their morphology and dissolution pattern. The method employed is a spray drying technique with polymer sodium carboxymethylcellulose (SCMC) or hyaluronan (HA) as the polymer encapsulating material for the drug. The concentration of AgSD used was 1% w/v while the concentration used for the polymer was 2.5% w/v for SCMC and 0.75% w/v for HA. The morphology of the microcapsules obtained was determined under scanning electron microscope. The dissolution rates of the two different microcapsules were studied in deionised water at a fixed temperature of 37°C over 72 h with the unprocessed AgSD as a control. The result, showed that microcapsules were formed for the two different polymers with a typical 'dimple' like characteristics. The dissolution rate was increased by 60 percent for microcapsules with SCMC as polymer and 115 percent increased were determined for microcapsules with HA as polymer compared to their respective controls. The study suggests that microcapsules of HA containing AgSD are more likely to give a better therapeutic effect when applied locally because of its higher dissolution rate.